Análise metagenômica de comunidades microbianas do aparelho genital de bovinos sadios e acometidos por distúrbios reprodutivos - Rodrigues, Nureyev Ferreira (2013)
Reproductive disorders in bovines can be caused by various pathogens, which might already be present in the reproductive tract. The microbial community of the reproductive apparatus, when known, can provide information about the health of the host. The metagenomics has been used to characterize and obtain genetics information about microbial communities in various environments and can relate certain diseases with changes in community composition. In this study, samples were collected from the secretion of mucosa of vaginal surface of 05 healthy cows and 05 cows that showed symptoms of reproductive disorders. Metagenomics DNA samples were extracted of secretion samples and amplified with primers for the V5-V6 regions of the 16S rRNA and sequenced on the platform "Ion Torrent Personal Genome Machine - PGM". The data were processed to remove low quality sequences and chimeras, with the Mothur program, then the data were released in the Ribosomal Database Project for classification of OTU's. Local blastn was performed and this results was loaded in MEGAN program, for viewing profiles and taxonomic microbial attributes. The control profile showed a total of 15 taxa, being the taxa Bacteroides, Enterobacteriaceae and Victivallis, with the highest representation of OTU's; the positive profile showed 68 taxa, and Bacteroides, Enterobacteriaceae, Histophilus, Victivallis, Alistipes and Coriobacteriaceae, the taxa with more OTU's representation. The genus Histophilus have pathogenics species in reproductive tract of cattle. There was a change in the community composition, well as in microbial attributes of profiles there may be a relationship between the pathogen and of other representatives taxa, in production of metabolites to disease progression.